Da misericórdia à misericórdia/ justiça em Lucas. O encontro com a viúva de Naim (Lc 7,11-17) - Amaral, Junior Vasconcelos do (Revista Eclesiástica Brasileira, 2020)
Este artigo1 visa compreender o significado dos termos misericórdia e justiça no Evangelho de Lucas. No encontro de Jesus com a viúva de Naim, marcado pela misericórdia/justiça, pode-se averiguar a riqueza semântica da narrativa lucana. Observa-se que no horizonte teológico de Lucas a misericórdia está imbricada a justiça, pois, ao agir com misericórdia para com a viúva, Jesus está cumprindo a justiça de Deus. A teologia lucana conduz seu leitor a perceber que, para Jesus, misericórdia significa “vontade de salvar”; por isso ele age com compaixão, “comovendo-se”. Nota-se em Lucas que o termo hebraico HeSeD, de léxico grego ἐσπλαγχνίσθη [esplanchnisthē], pode ser traduzido por “compadeceu-se”. Ao devolver a vida ao jovem, Jesus recupera a esperança da viúva, suprimida pelo desalento. Sua açao, da misericórdia para a misericórdia/justiça, revolve o coração da mulher viúva de Naim; o ato transformador desempenhado por Jesus remove o desalento, a dor e devolve o alento e a alegria. Na obra lucana, ele age com misericórdia/justiça para com todos os que estão na dor, na morte ou em qualquer realidade injusta. Ele e o novo profeta de Israel que instaura a misericordia/justica de Deus (Lc 7,16). Abstract: The aim of this article is to understand the meaning of the term’s mercy and justice in the gospel of Luke. In the encounter of Jesus with the widow of Naim, marked by mercy/justice, one can ascertain the semantic richness of the Lucan narrative. In Luke, it is observed that in his theological horizon, mercy is interwoven with justice, because in acting with mercy towards the widow, Jesus is fulfilling the justice of God. Lucan theology leads its reader to realize that, for Jesus, mercy means “will to save”, that is why he acts with compassion, with pity. It is noted in Luke that the Hebrew term HeSeD, from the Greek lexicon ἐσπλαγχνίσθη [esplanchnisthē], can be translated as “having pity on”. By returning the young man to life, Jesus revives the hope of the widow, suppressed by discouragement. The action of Jesus, from mercy to mercy/justice, enraptures the heart of the widowed woman of Nain. The transforming act performed by Jesus removes discouragement, pain and returns vigor and joy. In the Lucan work, Jesus acts with mercy/justice towards all who are in pain, in death or in any unjust reality. He is the new prophet of Israel who establishes God’s mercy/justice (Lk 7,16). Keywords: Gospel of Saint Luke; Mercy; Justice; Compassion.